Genome-wide profiling of RNA polymerase II and associated co-transcriptional processes using advanced NET-seq data - Gomes, Tomás Pires de Carvalho (2018)
Tese de mestrado, Bioinformática e Biologia Computacional (Biologia Computacional), Universidade de Lisboa, Faculdade de Ciências, 2014